INCLUSIVE CULTURE IN MAINSTREAM SCHOOLS (Annual of the Faculty of Philosophy in Skopje, 2009)
Inclusive education is a rationale concept which means wholeness and long transformation of institutional systems in society, especial in education. There are a number of important and unresolved issues relating to inclusive education in theoiy and practice.With this article we like to consider the important of continued development of inclusive cultures in mainstream schools. There are many arguments that inclusive culture is most inßuential aspect of inclusion. If the culture and the climate are not inclusion-friendly then the outcome, irrespective of polices or indeed practices, may not be successful. Results from analyse of attitude of educational staff and parents, and analyse of low, implicated a need of more attend on this aspects, in further. Inclusive cultures, police and practices are important aspects for successful inclusion of students with special needs in regular school.
Keywords: Inclusion; Inclusive culture